Annatto concentrate reduces oxidative stress in ewes during metabolic challenge stages - Guimarães, Leticia Jalloul; da Silva, Isabella Guartieri; Sena, Gabriella Capitane; Lourenço, Gabriel; Azoia, Isabella Pereira; Simonelli, Sandra Maria; De Almeida Rego, Fabiola Cristine; Damasceno, Débora Cristina [UNESP]; Zundt, Marilice (Elsevier, 2025)
This study evaluated the effects of annatto concentrate (ANC) supplementation on oxidative stress markers in ewes during critical reproductive phases: prepartum, postpartum, and weaning. Thirty Dorper crossbred ewes were divided into three groups (n = 10): Control (0 % ANC), 0.5 % ANC, and 1 % ANC. Blood samples were collected at three stages: last third of gestation (100 days), postpartum, and weaning, and analyzed for TAC, MDA, reduced thiols (-SH), hydrogen peroxide (H₂O₂), and the enzymatic activities of catalase, superoxide dismutase (SOD), and glutathione peroxidase (GPx). Results indicated that the 1 % ANC dose significantly reduced H₂O₂ and MDA levels during prepartum period (P < 0.05), while the 0.5 % dose enhanced catalase activity during postpartum (P < 0.01). At weaning, the 0.5 % ANC dose also improved oxidative status by increasing SOD and GPx activity (P < 0.05). These findings suggest that ANC supplementation improves oxidative balance in ewes during metabolically demanding periods, offering a natural strategy to enhance animal health and welfare.